2017
DOI: 10.3390/ijms18081809
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic Acid from Pear Inhibits Melanogenesis in Melanoma Cells

Abstract: Despite the critical role of melanin in the protection of skin against UV radiation, excess production of melanin can lead to hyperpigmentation and skin cancer. Pear fruits are often used in traditional medicine for the treatment of melasma; therefore, we investigated the effects of pear extract (PE) and its component, protocatechuic acid (PCA), on melanogenesis in mouse melanoma cells. We found that PE and PCA significantly suppressed melanin content and cellular tyrosinase activity through a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Regarding inhibition of tyrosinase activity, G. pfeifferi was the most effective fungal species (15.89 mg KAE/g extracts), followed by G. resinaceum (14.76 mg KAE/g), G. applanatum (14.58 mg KAE/g), and G. lucidum (12.74 mg KAE/g). The presence of protocatechuic and chlorogenic acids in G. pfeifferi extract could justify the anti‐tyrosinase activity performed in the present study [45,46] . Contrary to our results, previously published data did not show any inhibitory effects of G. applanatum and G. recinaceum H 2 O extracts on tyrosinase activity [7] .…”
Section: Resultscontrasting
confidence: 99%
“…Regarding inhibition of tyrosinase activity, G. pfeifferi was the most effective fungal species (15.89 mg KAE/g extracts), followed by G. resinaceum (14.76 mg KAE/g), G. applanatum (14.58 mg KAE/g), and G. lucidum (12.74 mg KAE/g). The presence of protocatechuic and chlorogenic acids in G. pfeifferi extract could justify the anti‐tyrosinase activity performed in the present study [45,46] . Contrary to our results, previously published data did not show any inhibitory effects of G. applanatum and G. recinaceum H 2 O extracts on tyrosinase activity [7] .…”
Section: Resultscontrasting
confidence: 99%
“…The reports stated that trough the suppression of melanogenic enzymes and microphthalmia-associated transcription factor (Mitf) in α-melanocyte stimulating hormone-stimulated mouse melanoma cells PCA can decrease melanin content and cellular tyrosinase activity. 37 A study in Spain also investigated the anti-collagenase activity of FA by measuring antioxidant defense parameters based on their photoprotective ability. 38 In a review of FA concerning its cosmeceutical properties it was reported that the compound has the potential to inhibit melanin formation through competitive inhibition of tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the ES extract had strong antioxidant effects, inhibited tyrosinase, and regulated whitening-related protein expression. The activities might be attributed to gallic acid and protocatechuic acid detected in ES extract [ 33 , 34 ]. Therefore, ES appears to have the potential to be used for the development of natural cosmetics for skin whitening for effective reduction or prevention of excessive melanin pigmentation in the skin.…”
Section: Discussionmentioning
confidence: 99%